Parasitosis intestinales en niños de edad preescolar y escolar: situación actual en poblaciones urbanas, periurbanas y rurales en Brandsen, Buenos Aires, Argentina - Zonta, María Lorena (2007)
The present study describes the parasitoses in preschool and schoolchildren and the differences among urban (U), periurban (PU) and rural (R) areas of the Partido of Brandsen, Buenos Aires, Argentina. Faecal samples and anal brushed were collected in 119 children between 1 and 14 years old. The sedimentation (Ritchie) and flotation (Willis) techniques were used. Sixty three percent of the samples were parasited. The highest percentage of infection was seen in PU (80,8%), followed by R (63,4%) and U (55,8%). The comparisons among prevalences only indicated significant differences between PU and U (p=0,05; OR = 0,30; IC95%: 0,08-1,00). We identified Enterobius vermicularis (U: 28,8%; PU: 30,8%; R: 39%), Blastocystis hominis (U: 26,9%; PU: 46,2%; R: 31,7%), Entamoeba coli (U: 11,5%; PU: 15,4%; R: 9,8%); Giardia lamblia (U: 9,6%; PU: 34,6%; R: 7,3%); Ascaris lumbricoides (U: 9,6%; PU: 19,2%; R: 0%), T. trichiura (U: 9,6%; PU: 19,2%; R: 0%); Enteromonas hominis (U: 1,9%; PU: 0%; R: 2,4%); E. nana (U: 0%; PU: 7,7%; R: 4,9%); Iodamoeba butschlii (U: 0%; PU: 3,8%; R: 0%). Only G. lamblia was significantly higher in PU compared to U (p < 0,05; OR = 0,20; IC95%: 0,05-0,8) and R (p < 0,05; OR = 6,71; IC95%: 1,40- 42). Significant differences were observed between percentages of mono and poliparasitism in U (p < 0,05; OR = 4,48; IC95%: 1,18-18,82) and R (p < 0,01; OR = 10,39; IC95%: 2,36-51,99). PU had the highest value of poliparasitism (38,1%). The greatest level of parasitism in the periurban, which is characterized by the poorest living conditions, would suggest the negative impact of urbanization when it is not accompanied by the provision of basic infrastructure services.